Ion energy distribution functions in a dual-frequency low-pressure capacitively-coupled plasma: experiments and particle-in-cell simulation - Wang, Jun-Chieh; Tian, Peng; Kenney, Jason; Rauf, Shahid; Korolov, Ihor; Schulze, Julian (Plasma Sources Science and Technology, 2021)
Low-pressure (<10 s mTorr) multi-frequency capacitively coupled plasmas (CCPs) are essential for critical plasma processing applications such as high aspect ratio dielectric etching for 3D memory fabrication. As the processing requirements become more stringent for future microelectronics technologies, plasma simulations are being used to help design industrial CCPs with the goal of accurately controlling the ion energy and ratio of ion to radical flux. Experimental validation is critical for developing trust-worthy plasma models. In this paper, a 1D particle-in-cell (PIC) model is used to simulate the ion kinetics and sheath dynamics in low pressure (a few to 10 s mTorr) dual-frequency (100 s kHz to 10 s MHz) Ar CCPs. Experimental results are compared to the 1D PIC model over a range of conditions. With pressure as low as 2 mTorr, a double-peak IEDF is predicted by the model; as the pressure increases to 20 mTorr, the double-peak IEDFs gradually shift to an IEDF with a strongly depleted high energy tail due to the higher ion-neutral collision frequency. The high energy peak of the bimodal IEDFs shifts to higher energy with increasing low-frequency voltage while the low energy peaks remain unmoved. When the low-frequency increases, the width of the IEDFs reduces, and new peaks at low energy emerge. The IEDFs from the PIC modeling results agree well with measurements.